KINERJA KEUANGAN SEBELUM DAN SESUDAH PANDEMI COVID-19 PADA INDUSTRI HOTEL, RESTORAN DAN PARIWISATA DI BEI - Aritonang, Grace Gevani; Indriyani, Kristi (Politeknik Negeri Ambon, 2023)
In 2022 declared Covid-19 a global epidemic, Covid-19 had an impact on the medical, financial and economic sectors. This research was conducted to obtain empirical evidence of financial performance before 2018 and after Covid-19 until 2021 in the hotel, restaurant and tourism industry in Indonesia which are listed on the Indonesia Stock Exchange based on an analysis of profitability, solvency, liquidity, activity and market ratios . This type of research is a comparative study method with a quantitative descriptive approach with 20 samples. The analytical method will use statistical methods from the Statistical Package for the Social Science (SPSS) 25 application, with the current ratio, debt to equity ratio, net profit margin, total assets turnover, and earnings per share. The different test will be carried out using the Wilcoxon test based on data that is not normally distributed. From the results of this study it was concluded that there were significant differences during the Covid-19 pandemic. There was a decline in financial performance in the hotel, restaurant and tourism industries on the Indonesia Stock Exchange.